QoS-driven multicast tree generation using tabu search - Youssef, H. (2020)
Many multimedia communication applications require a source to transmit messages to multiple destinations subject to Quality-of-Service (QoS) delay constraint. The problem to be solved is to find a minimum cost multicast treee where each source to destination path is contrained by a delay bound. This problem to be solved is to find a minimum cost multicast treee where each source to destination path is constrained by a delay bound. This problem has been proven to be NP-complete. In this paper, we present a Tabu Search (TS) algorithm to construct a minimum cost delay bounded multiacst tree. The proposed algorithm is then compared with many existing multicast algorithms. Results show that on almost all test cases, TS algorithm exhibits more intelligent search of the solution subspace and is able to find better solutions than other reported multicast algorithms.